Pengaruh Fasilitas Belajar Dirumah Terhadap Prestasi Belajar Peserta Didik Kelas Tinggi di SD Inpres Tara-Tara 2 - Steven Mandey (Jurnal Ilmiah Wahana Pendidikan, 2021)
This study aims to determine and analyze the effect of learning facilities at home on the learning achievement of high-class students at Inpres Primary school of Tara-Tara 2, Tomohon Barat District, Tomohon City. This research is a quantitative research with the type of ex post facto research. Quantitative research is a method for testing certain theories by examining the relationship between variables. This method is called the quantitative method because the research data is in the form of numbers and the analysis uses statistics. Learning facilities at home have a positive effect on learning achievement, meaning that every addition to learning facilities at home will increase learning achievement. If there is a decrease in learning facilities at home, it will decrease learning achievement. This is reinforced and supported by a significance value smaller than the alpha value, namely 0.000 <0.05, meaning that learning facilities at home have a positive and significant effect on learning achievement. Furthermore, it can be seen that the results of t arithmetic are greater than t table, namely 4.400 > 2.018, meaning that H0 is rejected and Ha is accepted so this shows that learning facilities at home have a positive and significant influence on the learning achievement of high-class students at Primary school Inpres Tara-Tara 2. Learning facilities in the homes of high-class students at Primary school Inpres Tara-Tara 2 have an effect of 31.6% on the learning achievement of high-class students at Primary school Inpres Tara-Tara 2, while the rest is influenced by other factors not included in this study, which is 68.4 % means that the hypothesis Ha is accepted that learning facilities at home affect the learning achievement of high-class students at Primary school Inpres Tara-Tara 2.